External Borrowing by the Baltics, Russia and Other Countries of the Former Soviet Union : Developments and Policy Issues. (IMF Working Papers; Working Paper ;, 1997)
Many countries among the Baltics, Russia and other CIS states are increasingly borrowing on international capital markets, a development that generally reflects their success in achieving financial stabilization. In view of the low level of domestic saving and large capital requirements, recourse to foreign borrowing may of course generate significant benefits for these economies in transition. However, the rapid increase in external debt suggests that consideration also needs to be given to the risks from too high a dependence on foreign saving, including inter alia risk of the postponement of needed structural reforms.